Moldova Poverty Update - World Bank (Washington, DC, 2014)
Moldovan GDP growth rose and the poverty rate fell steeply following the end of the Russian financial crisis in 1999. Since late 2002, GDP has continued to grow vigorously, however there has been little progress in reducing poverty. In short, GDP growth is no longer reducing poverty. The national poverty rate is broadly stable while the rural poverty rate is on a modest upward trend. Analysis of data from the household budget surveys shows that the decline in the national poverty rate stopped at the end of 2002, and that the rate has been broadly stable since. The rural poverty rate has been on a modest upward trend; the increase in poverty is concentrated among farmers, and to a lesser extent, among rural pensioners. At the same time, real incomes rose among rural wage earners. Real incomes also rose among urban residents, and their poverty rate continued to decline, as they benefited from the expansion of the construction industry and from rising real wages in construction, manufacturing, and public service.